The effect of hypoxic training on developing speed Endurance and achievement for runners - Hilal, Saeed Alwan; Chaleefah, Rafaa Rashid (International Journal of Psychosocial Rehabilitation, 2020)
In the introduction, the researcher Endurance on the sporting achievements that continue in various sports, including athletics, which broke records from time to time, which indicates that there are efforts made by scientists and coaches in arriving at the best ways, means and methods to achieve new sporting achievements by conducting studies and research in This is scientifically proven, and because athletics with all their effectiveness is one of those activities that are widely popular all over the world due to its excitement and excitement in competition in reaching the fastest, highest and strongest in its effectiveness, the 400-meter running activity is one of the fast-running activities that are classified Among the activities that are performed with the maximum speed and less than the maximum and due to their relative long distance, they need physiological requirements and physical ability commensurate with their performance and the energy system working in them, which is the non- oxygenic energy system. It helps improve the adequacy of runners' functional devices and raises their susceptibility.One of the uncommon methods at the local level is the hypoxic training, which means the lack of oxygen in the muscular tissues, especially the working ones. Therefore, the importance of this study shows the use of hypoxic exercises in developing a complex physical ability which carries the speed of the 400-meter running effectiveness as well as in its completion.The research problem, there are many methods and methods that are used in training, and hypoxic (hypoxia) is one of the methods used in training internationally, especially in activities that are characterized by high intensity and oxygen deficiency occurs and after the researcher polled the opinions of some coaches, experts and players, I found that this means and this type Training is uncommon at the local level, especially for speed Endurance and 400 meters running. Therefore, it is necessary to think about finding methods, methods and training methods that raise the sufficiency of the functional and physical equipment of the player to continue his performance with high intensity, resisting fatigue and lack of oxygen, so the researcher decided to conduct a field study using hypoxia exercises in the blood (hypoxic) using an oxymeter to measure the rate of oxygen deficiency Which is used for the first time in training locally and that was imported from the United States of America, aswell as the use of masks for the mouth and nose to impede the inhalation of air as well as the use of a little rest between exercises with a heart rate indicator that is not returned in a way that meets the body’s need of oxygen consuming that will be 140 z /Dr.And the use of these exercises in developing special speed Endurance and completing a 400- meter run, a modest contribution from the researcher in the use of this type in the 400-meter running training.Research Objectives: Developing hypoxic exercises in developing special speed Endurance and achievement for runners. Knowing the effect of hypoxic exercises in developing special speed Endurance . Identifying the effect of hypoxic exercises in accomplishing a 400-meter run..